A constitutive model of nanocomposite hydrogels with nanoparticle crosslinkers. (September 2016) - Wang, Qiming; Gao, Zheming
Abstract: Nanocomposite hydrogels with only nanoparticle crosslinkers exhibit extraordinarily higher stretchability and toughness than the conventional organically crosslinked hydrogels, thus showing great potential in the applications of artificial muscles and cartilages. Despite their potential, the microscopic mechanics details underlying their mechanical performance have remained largely elusive. Here, we develop a constitutive model of the nanoparticle hydrogels to elucidate the microscopic mechanics behaviors, including the microarchitecture and evolution of the nanoparticle crosslinked polymer chains during the mechanical deformation. The constitutive model enables us to understand the Mullins effect of the nanocomposite hydrogels, and the effects of nanoparticle concentrations and sizes on their cyclic stress–strain behaviors. The theory is quantitatively validated by the tensile tests on a nanocomposite hydrogel with nanosilica crosslinkers. The theory can also be extended to explain the mechanical behaviors of existing hydrogels with nanoclay crosslinkers, and the necking instability of the composite hydrogels with both nanoparticle crosslinkers and organic crosslinkers. We expect that this constitutive model can be further exploited to reveal mechanics behaviors of novel particle-polymer chain interactions, and to design unprecedented hydrogels with both high stretchability and toughness.